Management městského úřadu Přerov - Jemelková, Martina (Univerzita Pardubice, 2006)
Práce se zabývá managementem konkrétního subjektu veřejné správy – Městského úřadu Přerov. Pozornost je věnována analýze spokojenosti zaměstnanců Městského úřadu Přerov se svým zaměstnavatelem.

This thesis deals with a management of a particular public administration – Municipal Council in Přerov. The main chapter of this thesis represents an analysis of satisfation of the Municipal Council employees towards their employer.
Management of the municipal council in Přerov
Keywords: Public Administration; managements; public administrations; municipal council of Přerov; Questionnaires; Management; veřejné sektory; městský úřad Přerov; dotazníky; veřejná správa